2015
DOI: 10.1016/j.jocn.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of multivariate linear regression and support vector regression to predict functional outcome after surgery for cervical spondylotic myelopathy

Abstract: This study introduces the use of multivariate linear regression (MLR) and support vector regression (SVR) models to predict postoperative outcomes in a cohort of patients who underwent surgery for cervical spondylotic myelopathy (CSM). Currently, predicting outcomes after surgery for CSM remains a challenge. We recruited patients who had a diagnosis of CSM and required decompressive surgery with or without fusion. Fine motor function was tested preoperatively and postoperatively with a handgrip-based tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Table 3 shows that SVR with a radial kernel, which is a nonlinear regression model, performs better than the two linear models (MLR and SVR with a linear kernel). This demonstrates that the relationships between the predictors and the ODI scores can be more accurately described using nonlinear functions, which partially agrees with the findings in Hoffman et al [42]. The reported estimation accuracy (MAD = 0.12 and r = 0.76) can be achieved when FirstQMeanErr, ∆Gain, and VEL-INC are used to construct an SVM-based model.…”
Section: Estimation Of Perceived Motor Deficitssupporting
confidence: 90%
See 2 more Smart Citations
“…Table 3 shows that SVR with a radial kernel, which is a nonlinear regression model, performs better than the two linear models (MLR and SVR with a linear kernel). This demonstrates that the relationships between the predictors and the ODI scores can be more accurately described using nonlinear functions, which partially agrees with the findings in Hoffman et al [42]. The reported estimation accuracy (MAD = 0.12 and r = 0.76) can be achieved when FirstQMeanErr, ∆Gain, and VEL-INC are used to construct an SVM-based model.…”
Section: Estimation Of Perceived Motor Deficitssupporting
confidence: 90%
“…Nonetheless, the reported results demonstrate that the handgrip device and algorithms can together quantify the hand motor function with close correlation to the level of perceived deficits in performing ADL with acceptable accuracy. The estimated ODI scores, as well as the actual ODI scores that were collected postoperatively, showed statistically significant correlation to arm pain duration (p < 0.007 and p < 0.006, respectively), which agrees with findings in prior work [42]. Table 3 shows that SVR with a radial kernel, which is a nonlinear regression model, performs better than the two linear models (MLR and SVR with a linear kernel).…”
Section: Estimation Of Perceived Motor Deficitssupporting
confidence: 87%
See 1 more Smart Citation
“…We chose this activity because it requires coordinated manipulation of grip strength (including active muscle contraction and relaxation) that is abundant in the ADLs. Moreover, this test has previously shown to be feasible and efficacious in measuring fine motor function of patients with other neurologic disorders [15, 27]. We observed a significant improvement in accuracy on our handgrip-based tracking task over time.…”
Section: Discussionsupporting
confidence: 56%
“…To this end, multiple groups have recently published articles on the use of ML in predictive modelling related to both DCM and nontraumatic lumbar SCI. One of the early articles on applying ML to DCM was published by Hoffman and colleagues, 35 who compared a support vector regression model (SVR -a regression variant of SVM) with a multivariate logistic regression model in the prediction of functional outcome (specifically, the Oswetry Disability Index or ODI) after surgery for DCM. The authors found that the SVR model outperformed its logistic regression counterpart.…”
Section: Machine Learning Algorithms In Nontraumatic Spinal Cord Injurymentioning
confidence: 99%